Islamic Sosial Finance Untuk Mencapai Pembangunan Berkelanjutan Melalui Instrumen Ziswaf Ditinjau Dari Pemikiran Abu Ubaid - Lestari, Lisa Yuni; Adlan, Muhamad Aqim; Aswad, Muhammad (Wacana Equiliberium (Jurnal Pemikiran Penelitian Ekonomi), 2025)
The utilization and management of Islamic Social Finance (ISF) in Indonesia is currently not optimal, even though the potential revenue is very high. This research examines alternative solutions and strategic priorities for implementing ISF to support sustainable development in both the short and long term. The method used is a descriptive qualitative approach by collecting data from various secondary sources. This research highlights several important updates: first, the management of zakat and waqf can reduce poverty and hunger. Second, the implementation of these Islamic thinkers can create a society with quality education, access to clean water, decent work, economic growth, reduced inequality, and a healthy and prosperous life in the future. All these points are in line with sustainable development goals. Keywords: Islamic Social Finance, Ziswaf, philanthropy, poverty development